Monitoring and evaluating climate change adaptation and disaster risk reduction in Uganda: TAMD appraisal study - Kabesiime, Edith; Owuor, Charles; Barihaihi, Margaret; Kajumba, Tracy (International Institute for Environment and Development, 2022)
Climate change is one of the most important global issues, with broad and far reaching ecological, social, economic, and political impact. Uganda is already experiencing impacts of climate variability and climate change manifested through change of weather patterns and resultant disasters including prolonged droughts, floods and high temperatures. There are several ongoing adaptation and mitigation interventions aimed at reducing vulnerability to the impacts of climate change. To understand the value or efficacy of these interventions, sound monitoring and evaluation of these interventions is imperative for ensuring results, cost effectiveness, and impact-level outcomes. Despite this recognition, and where as funding of adaptation activities especially for developing countries is now the major focus of international climate negotiations and domestic climate policy, there is increasing concern about the inadequate approaches, frameworks and tools for monitoring and evaluating adaptation. This report therefore presents findings of a scoping study undertaken by independent consultants on behalf of the International Institute for Environment and Development (IIED) to provide a basis for developing a national framework for tracking climate change adaptation and DRR (Disaster Risk Reduction) interventions in Uganda. Study methods included review of key policy documents and related literature and interviewing of key informants at ministry level, sector/subsector level as well as at district level. Government ministries andother development agencies such as United Nations Development Programme (UNDP), Africa Climate Change Resilience Alliance (ACCRA) and selected Non Governmental Organisations (NGOs) that are currently working closely with government on adaptation and DRR initiatives were also gathered into a one day stakeholders’ workshop to validate the preliminary findings and to help fill information gaps. Overall, the study found that Uganda has an adequate policy and institutional framework for monitoring and evaluation that could provide a viable entry point for developing a framework for tracking climate change adaptation and DRR. Institutional roles are stipulated in the national policy for Public sector monitoring and evaluation. The government has also developed a number of tools and systems for data and information collection, processing, reporting, storage and dissemination. While the policy and institutional framework for public sector monitoring and evaluation are progressive, climate change and DRR are relatively new subjects which are not yet adequately addressed within these existing frameworks. Hence, many sectors, even those highly sensitive to climate change neither plan for nor report on climate change adaptation and DRR. Furthermore, the study reveals existence of different M&E frameworks and tools in different ministries and institutions, and no specific M&E framework in place and being used for climate change adaptation and DRR in Uganda. On a more positive note, the government with support from the French Development Agency (ADETEF) is developing the first National Performance Measurement Framework (PMF) for Adaptation based on the National Climate change policy and its implementation strategy. The PMF presents a strategic and useful entry point for the TAMD process. Existing M&E frameworks being used include; the Output Budget Tool (OBT) by Ministry of Finance, the score card by the Office of Prime Minister (OPM), the performance assessment tool for local governments, the Uganda Bureau of Statistics Management Information System and other data bases. Another key observation from this study is that existing government M&E tools in use tend to focus on output indicators without evaluating the outcomes for long term impact. Adaptation is long term, so the kind of monitoring being done might need reinforcement with TAMD process to add long term monitoring considerations which is in line with the Uganda National Development plan (2015/16–2019/20) and Vision 2040. Although this study did not go into in-depth capacity needs assessment, it notes general inadequate knowledge, awareness and technical capacity for climate change adaptation and risk reduction and how to report progress especially at the district level. On the other hand there is considerable appreciation at national lever, particularly within the Ministry of Local Government where a special committee composed of senior staff has been constituted to facilitate mainstreaming of climate change and disaster risk reduction in the ministry’s strategies and programmes.